Повсякденний світ професійної спільноти як поле історичного дослідження: основні методологічні підходи (Серія: Історія. Політологія, 2021)
У статті розглянуто теоретико-методологічні підходи, які дозволяють вивчити повсякденний світ професії як предмет міждисциплінарного історико-антропологічного дослідження. У публікації проаналізовано теоретичні здобутки філософії, соціології, антропології, культурної антропології, антропології професій, що уможливлюють здійснення методологічного синтезу з метою студіювання повсякденного життя професійної групи у соціальному й темпоральному контекстах. The article covers methodological-theoretic approaches to study a day-to-day world of a profession as a subject of interdisciplinary historical-anthropological research. Theoretical achievements in philosophy, social science, anthropology, cultural anthropology, anthropology of a profession were analyzed in the article, which enables methodological synthesis execution to characterize professional group routine in social context.Structural-anthropological approach serves to define the components of worth and symbolism, conceptual factors of a daily working routine of a professional, determined by peculiarities of a professional working cycle.The concept of «detailed description», which was introduced as one of the approaches, gives a chance to examine a person who is in a certain historical-social reality and who is constantly changing by gaining a different background and professional experience as well. Functionality has given special cognitive status to the profession as a social institution.Structural-functional and interactional approaches have given creative impulse to empirical research of professions, enlarging the subject concept by adding studies on marginal working activities, professional subcultures, influence of local contexts on professional surroundings.Phenomenology makes it possible to study daily practices that stand in and beside professional activity from an individual perception.Social study’s approach shows the impact of a profession on people’s behavior and reflexology of professional groups stating that each profession requires corresponding mental accommodation. Similar cognitive emotional behavioral reactions form special professional identity, which could be examined in social-spatial and social-temporary dimensions.